The Annexation of the Autonomous Republic of Crimea and the Armed Conflict in Eastern Ukraine as a Crime of Aggression by the Russian Federation against Ukraine - FRIS, Pavlo L.; MEDYTSKYI, Ihor B.; MYKYTYN, Yurii I.; SHPILIAREVYCH, Viktoriia V. (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019, 2019)
After the First World War, the international community gradually began to change their attitude to the question of the ‘legality’ of military conflicts. The article is devoted to the fact that the annexation of the Autonomous Republic of Crimea by the Russian Federation and the ongoing anti-terrorist operation in the Eastern regions of Ukraine testify to the transformation of Ukraine into an object of geopolitical confrontation, the edge of the planned activities of other international actors aimed at achieving its ambitious objectives. The purpose of the research is the study of criminal manifestations in the territory, annexed by the Russian Federation the Autonomous Republic of Crimea (hereinafter-ARC) and in the zone of armed conflict in the East of Ukraine, for the further development of effective mechanisms to counter the phenomena of political crime. the stabilization of the situation in the country. The methodological framework of this study consists of a set of modern scientific methods, the use of which is objectively determined by the relevance and purpose of the objectives of the study. The authors of the study recommend to strengthen the international response to the occupation and annexation by the Russian Federation in Crimea and waging an armed conflict in the East of Ukraine.